Designing Meaningful and Relevant Activities to Enhance Students’ Motivation during Covid-19 Pandemic - Andreas - Winardi (SAGA: Journal of English Language Teaching and Applied Linguistics, 2021)
Teachers and students all over the world are now facing the biggest shift in their lives, from studying in the school to studying at home, from meeting their teachers and friends face to face to meeting them via technology, and from depending on teachers to give them knowledge to depend on themselves. This change is not easy to cope with, both teachers and students are at their wit’s end. They are confused what to do and if this continues, they will be frustrated and lose their motivation for learning. Many parentscomplain that their children have to do a lot of assignments that overwhelm them. As a result, they lose motivation. To remedy this situation, teacher needs to design activities which are relevant and meaningful to their students.